2021
DOI: 10.7150/ijbs.52375
|View full text |Cite
|
Sign up to set email alerts
|

βII spectrin (SPTBN1): biological function and clinical potential in cancer and other diseases

Abstract: βII spectrin, the most common isoform of non-erythrocyte spectrin, is a cytoskeleton protein present in all nucleated cells. Interestingly, βII spectrin is essential for the development of various organs such as nerve, epithelium, inner ear, liver and heart. The functions of βII spectrin include not only establishing and maintaining the cell structure but also regulating a variety of cellular functions, such as cell apoptosis, cell adhesion, cell spreading and cell cycle regulation. Notably, βII spectrin dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 149 publications
(215 reference statements)
2
44
0
Order By: Relevance
“…Another ubiquitously present protein βII spectrin was found to be downregulated in severe COVID-19. Given that inadequate βII spectrin might precipitate into arrhythmia, heart failure, or even neurodegeneration (Yang et al, 2021), the findings hold much importance. Two proteins, namely, APOM, known to protect the lungs and kidneys from injuries (Ding et al, 2020), and APOA2, were also downregulated; similar observations were previously reported (Shen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another ubiquitously present protein βII spectrin was found to be downregulated in severe COVID-19. Given that inadequate βII spectrin might precipitate into arrhythmia, heart failure, or even neurodegeneration (Yang et al, 2021), the findings hold much importance. Two proteins, namely, APOM, known to protect the lungs and kidneys from injuries (Ding et al, 2020), and APOA2, were also downregulated; similar observations were previously reported (Shen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…46 Our studies have demonstrated that a crucial factor in platelet biogenesis TPM4 47 is inhibited (FC-1.94, P < 0.001) in severe cases thereby providing novel biological insight into COVID-19 severity. Yet another ubiquitously present protein βII spectrin was found to be downregulated in severe COVID-19, given that inadequate βII spectrin might precipitate into arrhythmia, heart failure, or even neurodegeneration 48 the ndings hold much importance. Two proteins namely APOM which is known to protect the lungs and kidneys from injuries 49 and APOA2 were also downregulated, similar observations were previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…45 Our studies have demonstrated that a crucial factor in platelet biogenesis TPM4 46 is inhibited (FC-1.94, P < 0.001) in severe cases, thereby providing novel biological insight into COVID-19 severity. Another ubiquitously present protein βII spectrin was found to be downregulated in severe COVID-19, given that inadequate βII spectrin might precipitate into arrhythmia, heart failure, or even neurodegeneration 47 the ndings hold much importance. Two proteins, namely APOM, which is known to protect the lungs and kidneys from injuries 48 and APOA2, were also downregulated; similar observations were previously reported.…”
Section: Discussionmentioning
confidence: 99%